Nanodispersible ferromagnetic powder α-Fe synthesized from citrates of iron for medical applications - Boshytska, N.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
A nanodispersible ferromagnetic powder α-Fe with the complex of physical and chemical properties (phase composition, high specific surface, chemical stability in plasma of blood and tissue liquid, active dissolution in gastric juice, chemical cleanness) necessary for the use in medical aims is created. The method of low-temperature (350—400 °C) decomposition/renewal of salts of citrates in the environment of hydrogen allowed us to get a nanodispersible ferromagnetic powder α-Fe with the specific surface of 31.4 m2/g. Its physical and chemical stability in plasma of blood is higher, as compared to standard powders α-Fe 3.200.26 and carbonic-iron (6-09-3000-78). The high specific surface and magnetic properties allow us to recommend a ferromagnetic powder α-Fe as a magnetic basis in the creation of composition materials for medical applications.